Human side of enterprise - "Douglas , McGregor" (London, 1960)
ome years ago during a meeting of the Advisory Committee of MITS School of Industrial Management, Alfred Sloan raised some questions related to the issue of whether successful managers are born or made. I was aware-as he was-that his questions were not easily answered. The discussion, however, served to sharpen certain interests I had had for some time in a systematic examina tion of the many common but inconsistent assumptions about what makes a manager
Keywords: Public enterprises